Behavior of non-oil commodity prices - Borensztein, Eduardo...[et al] (IMF WashingtonUS, 1994)
Reviews some of the key characteristics of commodity prices that may be useful in formulating the policy response to commodity price shocks and in assessing the outlook for commodity prices over the near term. Provides an assessment of the economic fundamentals determining the decline in commodity prices. Reviews the main policy issues raised by the recent behavior of commodity prices.